Physicochemical characterization and antioxidant activity of honey with Eragrostis spp. pollen predominance. Issue 1 (25th September 2017) - Aazza, Smail; Elamine, Youssef; El‐Guendouz, Soukaïna; Lyoussi, Badiâa; Antunes, Maria D.; Estevinho, Leticia M.; Anjos, Ofélia; Carlier, Jorge D.; Costa, Maria C.; Miguel, Maria G.
Abstract: This study aimed to characterize the pollen and physicochemical profiles, and to evaluate the antioxidant capacity of six samples of Moroccan honey. The pollen grains of Eragrostis spp. were predominant in all samples (from a minimum of 46.58 ± 1.59% to 72.72 ± 2.43% as a maximum), exceeding the minimum (generally 45%) required for the monoflorality nomination of a honey sample, and suggestion a case of newly reported honey. The analyzed samples had low diastase activity and hydroxymethylfurfural (HMF) content. Potassium was the dominant element in practically all samples, except the sample with the highest Eragrostis spp. pollen percentage, which showed sodium predominance. The honey color ranged from water white to light amber, and positively correlated the concentrations of phenols, proline and the capacity for scavenging free radicals. However, great variability observed in all the analyzed parameters, and could not be explained by the variability of the Eragrostis spp. pollen percentage, which suggests a hypothesis of low concentrated nectar. Practical applications: The melissopalynological profile of honey is an important parameter for determining the type of honey (multifloral, monofloral, blossom, honeydew) and its relationship to the botanical and geographical provenance. There is generally a relationship between the pollen profile of honey and the biological properties. The physicochemical characterization, antioxidant activity and melissopalynological profile of Eragrostis honey was reported for the first time in this study. These data intend to contribute for the introduction of a new type of honey labeled as Eragrostis honey. At the same time, the evaluation of the antioxidant activity may also trigger the search of other biological properties with medicinal attributes for the new Eragrostis ssp. honey.